Strategi Humanistik Guru Pendidikan Agama Islam dalam Pembentukan Akhlak Siswa: Analisis Kualitatif - Fadilawati, Agisna; Cipta Rahman, Nabilah; Shofiyati, Nur; Baehaqi, Luqman; Syahi, Abdul (Jurnal Pendidikan Agama Islam Al-Thariqah, 2025)
This research explores the contribution of Islamic Religious Education (PAI) teachers in nurturing students’ character at SMKN 3 Buntok. The study aims to illustrate the strategies employed by these educators, the obstacles they encounter, and the methods they adopt to overcome them. Utilizing a qualitative research approach, data were gathered through interviews. The results reveal that PAI teachers serve as exemplary figures, advisors, and motivators by modeling positive behavior, instilling good habits, implementing life-related learning, and using persuasive communication. Key challenges include limited instructional time and the diversity of students’ backgrounds. These are addressed through humanistic and cooperative teaching practices. The study concludes that the active involvement of PAI teachers, along with collaborative support from the school community, plays a vital role in character education.